Bibliometric and visual analysis of global publications on kaempferol - Tang, Ruying; Lin, Longfei; Liu, Yuling; Li, Hui (Frontiers in Nutrition, 2024)
Kaempferol, a flavonoid found in numerous foods and medicinal plants, offers a range of health benefits such as anti-inflammatory, antioxidant, antiviral, anticancer, cardioprotective, and neuroprotective effects. Herein, a bibliometric and visual analysis of global publications on kaempferol was performed to map the evolution of frontiers and hotspots in the field. Using the search string TS = kaempferol, bibliometric data for this analysis was extracted from the Web of Science Core Collection database and analyzed using the VOSviewer, CiteSpace, and Scimago Graphica software. As a result, by February 26, 2024, 11,214 publications were identified, comprising articles (n = 10746, 96%) and review articles (n = 468, 4%). Globally, the annual number of kaempferol publications surpassed 100 per year since 2000, exceeded 500 per year since 2018, and further crossed the threshold of 1,000 per year starting in 2022. The major contributing countries were China, the United States of America, and India, while the top three institutes of the citations of kaempferol were the Chinese Academy of Sciences, Consejo Superio de Investigaciones Cientficas, and Uniersidade do Porto. These publications were mainly published in agricultural and food chemistry journals, food chemistry, and phytochemistry. The keywords frequently mentioned include phenolic compounds, antioxidant activity, flavonoids, NF-kappa B, inflammation, bioactive compounds, etc. Anti-inflammation, anti-oxidation, and anti-cancer have consistently been the focus of kaempferol research, while cardiovascular protection, neuroprotection, antiviral, and anti-bacterial effects have emerged as recent highlights. The field of kaempferol research is thriving.